Performance Analysis of a Swastika shaped MIMO Antenna for Wireless Communication Applications - Chowdary, Polavarapu Sushma; Panda, Sampad Kumar (Engineering, Technology & Applied Science Research, 2025)
A novel wideband 4-port Multiple-Input Multiple-Output (MIMO) circular patch antenna is presented for operation in a resonant frequency band from 1.76 to 9.06 GHz used for PCs, Wireless Local Area Networks (WLANs) and satellite applications. The structure of the design consists of microstrip fed slot antenna considered on the four corners of the FR-4 substrate. To reduce mutual coupling and enhance the parameters of the MIMO antenna, a swastika-shaped ground is embedded. The simulated and experimental results show that the design achieves good performance, isolation >15 dB and radiation efficiency greater than 85%. The radiation patterns, surface currents, gain and channel capacity are also investigated. This circular shaped patch antenna is applicable to WLAN and satellite communication applications. Each circular patch on the four corners is connected to a 50 Ω microstrip feedline. A ring slot is etched on the circular patch and a small rectangular slot is embedded to the etched circular patch. The design provides good radiation patterns and the operating bands are obtained at 1.76 GHz, 2.4 GHz, 3.5 GHz and 9.06 GHz attaining reflection loss of -16 dB, -22 dB, -24 dB, -15 dB. The structure of the proposed design is simulated and evaluated in High-Frequency Structure Simulator (HFSS) software. The MIMO structure is fabricated on the FR-4 substrate. The minimum proximity between simulated and measured results is observed.